Learners’ Perceptions of the Benefits of Voice Toolbased Tasks on their Spoken Performance (GIST – Education and Learning Research Journal, 2014)
The purpose of this study is to investigate learners’ perceptions of the benefits of tasks using voice tools to reinforce their oral skills. Additionally, this study seeks to determine what aspects of task design affected the students’ perceptions. Beginner learners aged 18 to 36 with little or no experience in the use of technological tools for speaking practice were selected to participate in this study. The students’ reflections were analyzed by following a combination of qualitative and quantitative research approaches based on classroom observation and two surveys. The findings show that tasks using voice tools are beneficial for students’ oral performance as they can raise self-awareness and self-correction of speech patterns and provide extra practice of language features such as pronunciation, fluency, intonation and accuracy. The aspects of task design that affected the student’s perception of those benefits were the opportunity to work on self-awareness of their spoken performance, to interact for comprehension purposes, and to exchange information. Students acknowledged that voice tool-based speaking tasks can be educational, personally meaningful, enjoyable, and beneficial for the reinforcement of their oral skills as long as they are carefully planned and integrated into the dynamics of the class. It can be concluded that the asynchronous anxiety-free nature of voice tool-based speaking tasks offers several benefits to practice speaking skills both collaboratively and individually.
Keywords: voice tools; asynchronous computer-mediated communication (ACMC); communicative tasks; task design; speaking performance and competence